2012
DOI: 10.1123/jpah.9.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Yoga Practice and Physical Activity Following a Yoga Intervention for Adults With or at Risk for Type 2 Diabetes

Abstract: Background The current study described patterns of yoga practice and examined differences in physical activity over time between individuals with or at risk for type 2 diabetes who completed an 8-week yoga intervention compared with controls. Methods A longitudinal comparative design measured the effect of a yoga intervention on yoga practice and physical activity, using data at baseline and postintervention months 3, 6, and 15. Results Disparate patterns of yoga practice occurred between intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…18 20 21 25 28 29 32 33 35-40 Only five of these, however, reported maintaining a significant increase in PA from baseline at post-intervention follow-up 32 36 38-40 with four reverting to non-significant differences. 18 28 29 35 Furthermore, one study reported a significant increase in PA at the post-intervention follow-up but not at the end of the intervention 30 and another 27 had no significant changes in PA to report at the end of the intervention. In the studies that did not quantify PA, records of attendance were used to represent PA participation during the intervention period.…”
Section: Recruitment Planning and Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…18 20 21 25 28 29 32 33 35-40 Only five of these, however, reported maintaining a significant increase in PA from baseline at post-intervention follow-up 32 36 38-40 with four reverting to non-significant differences. 18 28 29 35 Furthermore, one study reported a significant increase in PA at the post-intervention follow-up but not at the end of the intervention 30 and another 27 had no significant changes in PA to report at the end of the intervention. In the studies that did not quantify PA, records of attendance were used to represent PA participation during the intervention period.…”
Section: Recruitment Planning and Implementationmentioning
confidence: 99%
“…Full references for included papers are therefore listed in the bibliography. Studies were located in the UK (n=10), 18-27 USA (n=5), [28][29][30][31][32] Canada (n=3), [33][34][35] Norway (n=2), 36 37 Italy (n=1), 38 Switzerland (n=1) 39 and South America (n=1). 40 Nearly all the studies were quantitative experimental studies in design, with 9 randomised controlled trials, 18 27-30 32 33 35 40 2 nonrandomised controlled trials 25 37 and 11 before-andafter studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking note of the rapid, visible expansion of yoga studios in American cities, I explore the role of yoga as a social determinant of urban health and yoga's entanglements with race and class identities. Evidence-based research has substantiated the beneficial effects of yoga on physical afflictions including asthma, diabetes, high blood pressure, obesity, rheumatoid arthritis, and in managing other painful conditions including scoliosis (Manocha, et al, 2002;Guarracino, et al 2006;Alexander, et al, 2012;Telles, et al 2011;Cade, et al 2010;Monroe, 2010;Wren, et al 2011;Tillbrook, et a, 2011). Yoga has also proved helpful in treatment for psychological conditions such as depression and for stress management (Shapiro, et al 2007;Yoshihara, et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have reported an association between yoga and reduction in weight and BMI. [26][27][28][29] There are a number of potential pathways by which yoga may impact body weight regulation (Figure 1), and a brief review of the literature to highlight these potential pathways is included below. …”
Section: Body Weight Regulation and Obesitymentioning
confidence: 99%